Integrated Analysis of Differential Expression Profiles of miRNA and mRNA in Gonads of Scatophagus argus Provides New Insights into Sexually Biased Gene Expression - Yaling Lei; Kaizhi Jiao; Yuanqing Huang; Yuwei Wu; Gang Shi; Hongjuan Shi; Huapu Chen; Siping Deng; Guangli Li; Wenjing Tao; Dongneng Jiang (Animals)
The Scatophagus argus (S. argus) is a valuable aquaculture species in southern China, with females exhibiting significantly faster growth rates than males. However, the limited understanding of its sex determination and differentiation mechanisms poses challenges for sex-controlled breeding. MicroRNAs (miRNAs), key post-transcriptional regulators, are known to modulate critical pathways governing sex determination and differentiation across several vertebrates. However, there is currently no research on miRNAs related to sex determination and differentiation in S. argus. In this study, we analyzed the expression profiles of miRNA and mRNA in the gonads of adult S. argus using high-throughput sequencing. Our analysis identified 2210 miRNAs, including 482 differentially expressed miRNAs (DEMs) between sexes. These DEMs targeted 3340 differentially expressed genes (DEGs), generating 13,773 regulatory interaction pairs. The expression of some DEGs related to sex determination and differentiation was found to be either positively or negatively correlated with expression of DEMs that might regulate them. The novel_miR_110/Foxl2, novel_miR_802/Gdf9, and novel_miR_1263/Gdf9 show opposing differential expression trends, whereas sar-miR-143-5p-4/Gsdf, sar-miR-143-5p-5/Gsdf, and novel_miR_379/Sox3 show consistent trends. The regulatory relationship between miRNA and gene in the gonads does not seem to be conserved among different fish species. This work advances our understanding of the molecular mechanisms underlying the sexual dimorphism of gonadal gene expression in S. argus. The identified miRNA–gene interactions may serve as potential targets for future sex-control strategies, contributing to advancements in aquaculture practices for this species.